Anthropometry, physical performance, and motor coordination of medallist and non-medallist young fencers - Norjali Wazir, M. R. W.; Mostaert, M.; Pion, J.; Lenoir, M. (Archives of Budo, 2018)
Background and Study Aim: Fencing is a sport that relies on a complex intra play of numerous performance characteristics. Evaluation of these characteristics is important in the field of talent identification and talent development. Multidimensional test batteries have proven their value in different sports. The present study aimed to identify anthropometric, physical performance and motor coordination characteristics that discriminate medallist and non-medallist fencers.